2005
DOI: 10.1039/b503790e
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study of ALA-induced endogenous porphyrins in arthritic knee tissues: targeting rheumatoid arthritis PDT

Abstract: The inflamed synovium of rheumatoid arthritis exhibits many features typical for neoplastic tissue implying that the photodynamic therapy might be an efficient modality for chronic poliarthritis. The accumulation of endogenously produced porphyrins after administration of exogenous 5-aminolevulinic acid (ALA) in a rabbit model of rheumatoid arthritis was evaluated by fluorescence spectroscopy. Independent of the way, intravenously or intra-articularly, in which ALA was administered to the experimental animals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…Since there is no ideal minimally invasive method for ablating inflamed synovium in joints, particularly in the smaller joints, of patients with RA, there are numerous attempts to employ endogenous porphyrins for diagnostic and therapeutical purposes in rheumatology as well [6,[10][11][12][13]15,23,24,37]. In order to apply PDT on the inflamed synovium, it is essential to prevent cartilage damage to make it safe and suitable approach for treatment of inflammation of the joints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since there is no ideal minimally invasive method for ablating inflamed synovium in joints, particularly in the smaller joints, of patients with RA, there are numerous attempts to employ endogenous porphyrins for diagnostic and therapeutical purposes in rheumatology as well [6,[10][11][12][13]15,23,24,37]. In order to apply PDT on the inflamed synovium, it is essential to prevent cartilage damage to make it safe and suitable approach for treatment of inflammation of the joints.…”
Section: Discussionmentioning
confidence: 99%
“…This minimally invasive PDT approach could serve as an attractive alternative to the surgical synovectomy, because it usually results in little or no scarring and presumably would http shorten a rehabilitation period and reduce the need for subsequent physiotherapy. Resent findings showed that, besides inflamed synovium, endogenous porphyrins were also detected in cartilage tissues of rabbit rheumatoid arthritis model in vivo [23,24] and chondrocytes in vitro [25] after the application of ALA or its methyl ester (ALA-Me). In vitro study reported that the highest levels of PpIX fluorescence during flow cytometry measurements were detected in osteoblasts, followed by synovial cells and chondrocytes [25].…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, the sensitivity of osteoblasts might results in an adverse effect if bone tissue adjacent to a joint is subjected to 5-ALA-PDT, even though the involvement of bone has been reported to be limited [42]. In light of an in vivo application, the preferred route of delivery of 5-ALA (systemic, local) to target the inflamed articular joints still needs to be assessed, as previously outlined in a rabbit model of rheumatoid arthritis [8]. It is quite likely that the local application will be superior over the systemic.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response, and as a consequence the destruction of cartilage, could be reduced successfully in experimental animal studies and in humans [1][2][3][4][5][6][7][8][9][10]. This anti-inflammatory effect was attributed to the inactivation and/or ablation of the inflamed synovial tissue, which was targeted by PDT.…”
Section: Introductionmentioning
confidence: 99%
“…The nonfluorescent PS precursor 5-aminolevulinic acid (5-ALA, trade name Levulan®) enhances the intrinsic production of protoporphyrin IX (PPIX) in mitochondria, which is activated by light illumination (~ 635 nm) following accumulation at the treatment site leading to the effective generation of reactive oxygen species within treated cells and triggering cell death [17,68,69]. The clinical use of topically applied 5-ALA for PDT was first introduced in 1990 [70] and followed by a wide range of clinical and preclinical studies for the PDT treatment of bladder cancer [71][72][73], chronic polyarthritis [74], malignant glioma [75], nonmelanoma skin cancers such as actinic keratosis (in combination with fluorescence dosimetry) [69,76], Barret's oesophagus and even multidrug resistant leukemia, the latter without much success [77]. In 2013 Bader et al reported a clinical trial using hexaminolevulinate (HAL), a 5-ALA derivative, for the PDT of bladder cancer in humans.…”
Section: Progress In Photosensitizer (Ps) Developmentmentioning
confidence: 99%